2019
DOI: 10.9789/2175-5361.2019.v11i5.1242-1249
|View full text |Cite
|
Sign up to set email alerts
|

Non–Pharmacological Management of Delirium From The Perspective of Nurses in an Adult Intensive Care Unit / O Manejo Não Farmacológico do Delirium Sob a Ótica de Enfermeiros de uma Unidade de Terapia Intensiva Adulto

Abstract: Objective:The study's main purpose has been to identify non-pharmacological measures in the management of delirium described by nurses of an adult Intensive Care Unit (ICU). Methods: It is a descriptive exploratory study with a qualitative approach that was performed with nurses working at an ICU from a public hospital in Brazil. Data were collected through a semi-structured interview and analyzed by the Thematic Content Analysis. Results: Nurses have knowledge about delirium and bring several non-pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 8 publications
0
15
0
3
Order By: Relevance
“…De modo semelhante às falas dos participantes deste estudo, as medidas não farmacológicas utilizadas no manejo do delirium foram relatadas como prática na atuação de enfermeiros que atuam na terapia intensiva, com destaque para o diálogo com orientação cognitiva, uso de equipamentos como televisão, relógio, janelas com incidência de luz solar para localização do paciente no tempo e no espaço, manutenção do sono, controle da luminosidade e ruídos no ambiente, restrição do uso de contenção mecânica e a facilitação da presença do familiar ao lado do paciente, ademais os benefícios de intervenções não farmacológicas no tratamento do delirium são reconhecidos e fomentados por enfermeiros. (17)(18) Porém, apesar da recomendação de restrição de contenção mecânica, o presente estudo revelou que a intervenção é utilizada com frequência nos cuidados de enfermagem.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…De modo semelhante às falas dos participantes deste estudo, as medidas não farmacológicas utilizadas no manejo do delirium foram relatadas como prática na atuação de enfermeiros que atuam na terapia intensiva, com destaque para o diálogo com orientação cognitiva, uso de equipamentos como televisão, relógio, janelas com incidência de luz solar para localização do paciente no tempo e no espaço, manutenção do sono, controle da luminosidade e ruídos no ambiente, restrição do uso de contenção mecânica e a facilitação da presença do familiar ao lado do paciente, ademais os benefícios de intervenções não farmacológicas no tratamento do delirium são reconhecidos e fomentados por enfermeiros. (17)(18) Porém, apesar da recomendação de restrição de contenção mecânica, o presente estudo revelou que a intervenção é utilizada com frequência nos cuidados de enfermagem.…”
Section: Discussionunclassified
“…O conhecimento sobre o delirium é fundamental, para viabilizar medidas de prevenção e controle. (17) Para tanto, o uso de intervenção educativa contribui para ampliação do conhecimento e melhorias no que se refere às novas práticas de prevenção e monitorização do delirium em pacientes internados em terapia intensiva. (23) No processo de condução clínica desses pacientes a comunicação é reconhecida como fundamental, no entanto pode ser desafiadora com pacientes delirantes, principalmente os hiperativos.…”
Section: Discussionunclassified
“…Os pacientes mencionaram, também, desejo de maior autonomia e de poder de decisão sobre seu tratamento, sendo o cuidado pessoal um fator relevante para seu bem-estar. Os autores Eberle et al (2019) complementam com medidas que poderiam auxiliar na diminuição do uso farmacológico, as quais também estão dentro do espectro do cuidado humanizado. Sob a ótica dos enfermeiros participantes desta pesquisa, emergiram alguns procedimentos, tais como: orientação verbal no tempo e no espaço, bem como os dispositivos que auxiliam nessa localização; janelas que possam promover a incidência de luz solar; restrição do uso de contenção mecânica; evitar a privação de sono; facilitar a presença do familiar dentro do ambiente da UTI.…”
Section: Discussionunclassified
“…Regarding the studies on nurses, Powell et al 11 assessed the knowledge, attitude, and beliefs toward delirium of 27 American nurses working in burn ICUs and identified the nurses' strong support for nonpharmacological nursing interventions in preventing delirium and their support for reducing the use of pharmacologic interventions. In addition, Eberle et al 1 conducted qualitative interviews with 12 Brazilian ICU nurses regarding their knowledge, prevention, and management of patients with delirium and reported that some of the nurses perceived delirium to be a pathological sign and symptom related to the length of stay in the hospital, the presence of relatives in the ICU together with no use of mechanical restraints, and necessary restraints only when the safety of the patient was at risk and that the use of nonpharmacological interventions in the management of delirium benefitted the patient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prevalence of delirium ranges from 1% to 2% in the community but increases to up to 10% to 30% in elderly patients in the emergency department; In addition, the prevalence further increases to approximately 14% to 24% on the general medical unit and continues to rise to upward of 70% to 87% within the intensive care unit (ICU); 16% to 85% of patients in ICUs experience delirium, and one-third of critical patients have experienced delirium, which is a prevalent issue in the ICU. 1 O'Donoghue et al 2 even proposed as high incidence when 80% of patients in the ICU have delirium, which, is often underrecognized by ICU clinicians. For patients with delirium, ICUs are a strange and enclosed space that can easily disrupt their sense of space and time.…”
mentioning
confidence: 99%